Sentiment analysis of cash waqf using the SentiStrength lexicon-based approach - Maulida, Syahdatul; Akbar, Nashr; Kassim, Salina (Journal of Islamic Economics Lariba, 2025)
IntroductionCash waqf is getting popular due to its potential contribution to support socio-economic initiatives as well as its flexibility for donors to participate. Despite this, criticisms surrounding cash waqf are also increasing as the sector continues to expand, which might adversely affect sentiment among future donors. ObjectivesThis study aims to analyze sentiments and perceptions towards cash waqf and subsequently identify specific factors affecting public perceptions toward cash waqf. MethodA total of 242 Scopus-indexed scholarly publications related to cash waqf (1979–2025) were analyzed using the sentiment analysis model: the lexicon-based tool SentiStrength. Sentiment distribution, consistency, and model performance were compared to provide a comprehensive interpretation. ResultsThe findings indicate that neutral sentiment is the highest, with a percentage of 46%, followed by positive sentiment at 34% and negative sentiment at 20%. The positive sentiments include the permissibility of cash waqf from the Islamic perspective by Imam Zufar, the potential of cash waqf to enhance the productivity of immovable waqf assets, an innovative instrument for socio-economic development, the significant role of cash waqf in economic development, and the flexible use of cash waqf to support business ecosystems in diverse sectors. On the other hand, several negative sentiments towards cash waqf cover debates about the impermanence of money as an object of waqf, suboptimal performance of trustees (nazir), relatively low societal awareness and literacy, a mismatch between its potential and the realization, the utilization of cash waqf mostly for religious and social activities (not in productive sectors that may generate income), lack of standardized reporting for cash waqf management, and lack of transparency in reporting to the public.ImplicationsThe findings urge policymakers to tackle the negative sentiments by improving governance, enhancing public awareness, strengthening institutional management of cash waqf, and addressing transparency issues. By addressing these issues, growth of the waqf sector can be further enhanced and accelerated due to increased public trust and participation in cash waqf. Originality/NoveltyThis study offers a novel contribution to Islamic social finance research by applying sentiment analysis to a corpus of 242 Scopus-indexed academic articles focused on cash waqf. While previous studies have extensively explored the legal, operational, and financial dimensions of cash waqf, limited attention has been given to how this topic is framed and evaluated in scholarly discourse. By employing SentiStrength, a lexicon-based sentiment classification tool, this research identifies underlying positive and negative sentiment patterns within academic narratives, thereby uncovering dominant perceptions and concerns around cash waqf implementation.